Weak solutions for a strongly-coupled nonlinear system - Osmundo A. Lima; Aldo T. Louredo; Alexandro O. Marinho (Electronic Journal of Differential Equations, 2006)
In this paper the authors study the existence of local weak solutions of the strongly nonlinear system $$displaylines{ u''+mathcalAu +f(u,v)u = h_1 cr v''+mathcalAv +g(u,v)v = h_2 }$$ where $mathcalA$ is the pseudo-Laplacian operator and $f$, $g$, $h_1 $ and $h_2 $ are given functions.